2019
DOI: 10.1002/ange.201911300
|View full text |Cite
|
Sign up to set email alerts
|

Festkörper‐ und Gasphasenstrukturen sowie energetische Eigenschaften des gefährlichen Methyl‐ und Fluormethylnitrats

Abstract: Eine verbesserte Synthese fürd en einfachsten Salpetersäureester,M ethylnitrat, und eine neue Synthese fürF luormethylnitrat benutzen die Salzeliminierung der entsprechenden Iodmethane mit Silbernitrat. Beide Verbindungen wurden spektroskopischu nd durch Strukturbestimmung im Festkçrper von in situ erzeugten Kristallen mittels Rçntgenbeugung sowie in der Gasphase mittels Elektronenbeugung identifiziert. Die Fluorierung führt zu Strukturen mit kürzeren C-O-und N-O-Bindungen, hat eine energetischd estabilisieren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[ 11 ] More recent investigations showed that the replacement of a CH 3 with a FCH 2 moiety can lead to a drastic change in the physical‐ and sensitivity properties of a compound. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] More recent investigations showed that the replacement of a CH 3 with a FCH 2 moiety can lead to a drastic change in the physical‐ and sensitivity properties of a compound. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…The 19 F NMR resonance of FCH 2 N 3 is detected at –170.1 ppm as a triplet. Since the azide substituent is less electronegative than a nitrate substituent, which with its electronegativity lies between the OCN/NCO cyanates, the resonance of fluoromethyl azide is shifted to lower frequency compared to fluoromethyl nitrate (–155.9 ppm) , . The 14 N NMR resonances for fluoromethyl azide are observed at –135(N β ), –166(N γ ) and –297(N α ) ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical investigations for FCH 2 R (R = NCO, NCS, N 3 and CNO) further add to available information. Recently, our initial studies on the system fluoroiodomethane with selected silver salts enabled access to the corresponding fluoromethyl derivatives FCH 2 OClO 3 and FCH 2 ONO 2 . In this contribution we would like to study the reactivity of metal pseudohalides, i.e.…”
Section: Introductionmentioning
confidence: 99%